Interventions to Prevent Unintentional Injuries Among Adolescents: A Systematic Review and Meta-Analysis - Salam, Rehana A.; Arshad, Ahmed; Das, Jai K.; Khan, Marium Naveed; Mahmood, Wajeeha; Freedman, Stephen B.; Bhutta, Zulfiqar A. (Journal of adolescent health, 2016)
Globally, every day, ∼2,300 children and adolescents succumb to unintentional injuries sustained from motor vehicle collisions, drowning, poisoning, falls, burns, and violence. The rate of deaths due to motor vehicle injuries in adolescents is 10.2 per 100,000 adolescents. We systematically reviewed published evidence to identify interventions to prevent unintentional injuries among adolescents aged 11–19 years. We defined unintentional injuries as a subset of injuries for which there was no evidence of predetermined intent, and the definition included motor vehicle injuries, suffocation, drowning, poisoning, burns, falls, and sports and recreation. Thirty-five studies met study eligibility criteria. The included studies focused on interventions to prevent motor vehicle injuries and sports-related injuries. Results suggest that possession of a graduated driver license (GDL) significantly reduced road accidents by 19% (relative risk [RR]: .81; 95% confidence interval [CI]: .75–.88; n = 5). There was no impact of GDL programs on incidence of injuries (RR: .78; 95% CI: .57–1.06; n = 2), helmet use (RR: 1.0; 95% CI: .98–1.02; n = 3), and seat belt use (RR: .99; 95% CI: .97–1.0; n = 3). Sports-related injury prevention interventions led to reductions in the incidence of injuries (RR: .66; 95% CI: .53–.82; n = 15), incidence of injury per hour of exposure (RR: .63; 95% CI: .47–.86; n = 5), and injuries per number of exposures (RR: .79; 95% CI: .70–.88; n = 4). Subgroup analysis according to the type of interventions suggests that training ± education and the use of safety equipment had significant impacts on reducing the incidence of injuries. We did not find any study focusing on interventions to prevent suffocation, drowning, poisoning, burns, and falls in the adolescent age group. The existing evidence is mostly from high-income countries, limiting the generalizability of these findings for low- and middle-income countries. Studies evaluating these interventions need to be replicated in a low- and middle-income country–context to evaluate effectiveness with standardized outcome measures.